Potencial produtivo e qualidade das silagens de seis novos híbridos de girassol - Rafael Araújo de Menezes (2022)
The climate changes driven by greenhouse effect has increased the challenges to agribusiness in the tropics by reducing the forecast predictions of forage production. As a result, the regenerative agriculture and animal production practices have gained insights and importance. In this scenario, the sunflower (Helianthus annuus) crop shows promise due to its adaptive features and versatility intended for animal feed use. However, there is a wide productive, agronomic and nutritive value variation. Therefore, the aim of this study was to evaluate the yield potential and the quality of the silages of new six sunflower hybrids. In order to carry out this study, the hybrids BRS 323, BRS 415, BRS 417, BRS 321, ALTIS 99 e SYN 045 were planted in randomized blocks. Six plants of each block were randomly harvested for agronomical evaluation and extracted their parts (capitulum and steam+leaves). The rest of the plants were ensiled for nutritive value, in vitro gas production and degradation kinetic evaluations. The results showed that the capitulum was the most nutritive part of the plant, with high levels of protein, lipids and digestibility. The correlational study demonstrated the capitulum’s diameter (r=0,3031; p=0,0908), stand (r=0,4585; p=0,0183) and height of the plant (r=0,6165; p=0,0015) had a positive correlation with green mass. The hybrid BRS 321 presented lower lodging and damage losses, but low dry matter production. Also, the BRS 321 silages presented largest neutral detergent fiber content (54,2%) and lowest ammoniacal nitrogen content (14,3%). The hybrid BRS 417 silages had highest ether extract (18,3%) and ammoniacal nitrogen content (29,4%). In general, the silages presented satisfactory contents of dry matter and crud protein, the fiber fractions were relatively low, but presented high levels of lignificaton. The ALTIS 99 and SYN 045 were superior for stand, height and productivity, as well as for the total volume of gas produced and the accumulative gas produced of their silages. The silages of the hybrid BRS 415 were significantly inferior for gas produced and degradation parameters. The methane production was similar between the silages produced by the hybrids BRS 323, BRS 415, BRS 417, ALTIS 99 and SYN 045 silages. It was characterized by slow methane production, with average of 5,22 mg/g of dry matter degraded. Therefore, the hybrids silages evaluated can be used as a strategic toll in ruminants feeding, mainly in regions affected by water scarcity and high temperatures caused by climate changes. In additional, sunflower can be an important crop in the regenerative and sustainable practices cooperating with the environmental gas methane mitigation.